Population and Habitat Characteristics of Tarsius fuscus in Resort Mallawa Bantimurung Bulusaraung, South Sulawesi - Meylia, Safira Arda; Putri, Desi Amelia; Aldyansyah; Meo, Lorenzo Elton; Rahman, Reja; Laijanan, Theresia Avilla; Mustari, Abdul Haris (Department of Forest Resources Conservation and Ecotourism - IPB University, 2024)
Tarsius fuscus is one of the conservation priority wildlife in the Bantimurung Bulusaraung National Park (Babul National Park). This study aims to analyze the population and habitat characteristics of T. fuscus as one of the considerations in the conservation management of its population and habitat. This research was carried out in July 2021 in the forest around Bentenge Village and Samaenre Village, Resort Mallawa, Babul National Park. The method used was direct observation, calculation of the number of individuals for each group, and vegetation analysis at the meeting points of T. fuscus. Based on observations, the population size of 48 individuals from 13 groups was obtained with an overall population density of 0.109 individuals/Ha. The population density in the secondary dryland forest is higher than in the scrubland. The number of juvenile and infant in both land cover were low compared to the adults. T. fuscus was found in two types of habitat, there are secondary dryland forests (SDF) and scrubland with specific ranges of physical parameters. Based on vegetation analysis, SDF was dominated by the mana-mana tree (Blumeodendron kurzii) with an important value index (IVI) of 57.72%, while shrubland was dominated by kemiri tree (Aleurites moluccana) with an IVI of 40.75%. The two land covers are dominated by the Moraceae family and jambu air seedlings (Syzygium aqueum).